Log versus level in VAR forecasting: 16 Million empirical answers - expect the unexpected - Johannes Mayr; Dirk Ulbricht (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2007)
The use of log-transformed data has become standard in macroeconomic forecasting with VAR models. However, its appropriateness in the context of out-of-sample forecasts has not yet been exposed to a thorough empirical investigation. With the aim of filling this void, a broad sample of VAR models is employed in a multi-country setup and approximately 16 Mio. pseudo-out-of-sample forecasts are evaluated. The results show that, on average, the knee-jerk transformation of the data is at best harmless.
Keywords: C52; C53; 330; VAR-forecasting; logarithmic transformation